Professional C++ - Gregoire, Marc (Wiley, 2021)
Improve your existing C++ competencies quickly and efficiently with this advanced volumeProfessional C++, 5th Edition raises the bar for advanced programming manuals. Complete with a comprehensive overview of the new capabilities of C++20, each feature of the newly updated programming language is explained in detail and with examples. Case studies that include extensive, working code round out the already impressive educational material found within.Without a doubt, the new 5th Edition of Professional C++ is the leading resource for dedicated and knowledgeable professionals who desire to advance their skills and improve their abilities. This book contains resources to help readers:* Maximize the capabilities of C++ with effective design solutions* Master little-known elements of the language and learn what to avoid* Adopt new workarounds and testing/debugging best practices* Utilize real-world program segments in your own applicationsNotoriously complex and unforgiving, C++ requires its practitioners to remain abreast of the latest developments and advancements. Professional C++, 5th Edition ensures that its readers will do just that
Keywords: C++; Programmiersprachen